2007
DOI: 10.1123/rsj.31.2.107
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Constraint Negotiation to the Leisure Satisfaction of College Students in Campus Recreational Sports

Abstract: Satisfaction experienced during leisure activity plays an important role in continued leisure participation. Leisure participation is also affected by leisure constraints. In recent years, the idea of negotiating leisure constraints has emerged as an important area of research. The concept of constraint negotiation suggests that individuals use various methods to overcome constraints and participate in leisure activities. Although research has been done examining the leisure satisfaction of college students, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…There is a wide range of literature on the benefits of sportive and recreational activities for individuals (Bakırcıoğlu, 2010;Balcıoğlu, 2003;Churilla and Fitzhugh 2012;Godin, Sheeran, Conner, Belanger-Gravel, Gallani and Nolin, 2010;Arslan, 2013;Elkins, Beggs and Choutka, 2007;Emir, Gürbüz and Öncü, 2014;McEwen, 2001;Dindar, 2018;Lautenschlager, Cox, Flicker, Foster, Van Bockxmeer, Xiao, Greenop and Almedia, 2008;Kılıç and Arslan 2018;Akyürek, Kars and Bumin 2018;Kurt, Bayazıt, Keskin and Taşkıran 2018). Bakırcıoğlu (2010) has stated that sports have an important effect on the socialization of individuals, and that the body energy increased in adolescence is channeled through exercises with the help of sports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a wide range of literature on the benefits of sportive and recreational activities for individuals (Bakırcıoğlu, 2010;Balcıoğlu, 2003;Churilla and Fitzhugh 2012;Godin, Sheeran, Conner, Belanger-Gravel, Gallani and Nolin, 2010;Arslan, 2013;Elkins, Beggs and Choutka, 2007;Emir, Gürbüz and Öncü, 2014;McEwen, 2001;Dindar, 2018;Lautenschlager, Cox, Flicker, Foster, Van Bockxmeer, Xiao, Greenop and Almedia, 2008;Kılıç and Arslan 2018;Akyürek, Kars and Bumin 2018;Kurt, Bayazıt, Keskin and Taşkıran 2018). Bakırcıoğlu (2010) has stated that sports have an important effect on the socialization of individuals, and that the body energy increased in adolescence is channeled through exercises with the help of sports.…”
Section: Discussionmentioning
confidence: 99%
“…It should not be forgotten that sportive and recreational activities are some of the elements that keep different emotions and behaviors of students under control and ensure that they use time effectively and develop leisure time strategies. Elkins, Beggs and Choutka (2007) have reported that satisfying free time enables individuals to cope with constraints, which enhances participation in free-time activities. Hacıoğlu (2003) has emphasized that recreational activities should bring happiness, satisfaction, creativity, mental balance, character, competitiveness, mental capacity, freedom, a physical and mental fitness, and therefore, a broader worldview to the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Constraints were evigotiation can be ongoing from the outset of an acdent when the ocean created situations that were tivity. Authors, including Elkins et al (2007), not part of their interpretations of a comfortable found that constraints do not always preclude leiscuba dive. There were many occasions when consure participation.…”
Section: Samplementioning
confidence: 93%
“…A qualitative paradigm supports dif-once constraints to access have been negotiated (Elkins, Beggs, & Choutka, 2007;Little, 2000). ferent assumptions, including that multiple meanings can account for human actions and the In a quantitative study of recreational scuba diving, Todd (2004) found divers' experiences language that describes and interprets social behavior is often value laden (Lincoln & Guba, with constraints were inherent features of the activity.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of leisure related to physical activity, negotiation strategies could help college students increase their physical activity levels as well as usage of the SRSC. While little research has been done in this specific area, Elkins et al (2007) investigated the role of physical activity constraint negotiation strategies in leisure satisfaction among college students. Their results suggest that college students most commonly use physical activity negotiation strategies related to interpersonal relations and developing new skills.…”
Section: Negotiation Strategiesmentioning
confidence: 99%